Fouling control of a membrane coupled photocatalytic process treating greywater - Pidou, Marc; Parsons, Simon A.; Raymond, Gaelle; Jeffrey, Paul; Stephenson, Tom; Jefferson, Bruce (Elsevier Science B.V., Amsterdam., 2009)
Fouling in membrane coupled photocatalytic reactors was investigated in the case of greywater treatment by establishing the link between product type, dose, irradiation time and fouling rates in a cross flow membrane cell fitted with a 0.4 μm pore sized polyethylene membrane. Rapid fouling occurred only with shower gels and conditioners and was linked to changes in the organo-TiO2 aggregate size postulated to be caused by polymers within the products. Fouling was reduced to a negligible level when sufficient irradiation was applied demonstrating that the membrane component of the process is not the issue and that scale up and implementation of the process relates to effective design of the UV reactor
Keywords: Greywater; Photo catalysis; Titanium dioxide; Fouling